Keragaman Morfologi Cengkih Tuni (Syzygium Aromaticum L.) Di Kecamatan Tehoru, Kabupaten Maluku Tengah, Provinsi Maluku - Namakule, Mirda Yanti; Mahulette, Asri Subkhan; Matatula, Avia Jolanda (Universitas Wiralodra, 2024)
Clove Tuni is a superior local clove variety from Maluku, widely cultivated in Tehoru District, Central Maluku Regency. Until now, information on morphological diversity in Tuni clove populations in the region is still limited. This study aimed to inform the morphological diversity of Tuni cloves and their morphological characteristics. The research was conducted in three villages in Tehoru District, Central Maluku Regency: Haya, Tehoru, and Yaputih Villages. The clove plants characterized were >20 years old, where ten plant samples were taken from each village, so there were 30 plants. Hierarchical Cluster Analysis (HCA) results for 54 morphological characters obtained from two groups of Tuni cloves with a dissimilarity coefficient of 13% (87% similarity). The first group comprised ten plants with a similarity coefficient of 92% (8% dissimilarity). In contrast, the second group consisted of 20 plants, of which 11 plants had a similarity coefficient of 91.5% or 8.5% dissimilarity (group IIa), and nine plants had a similarity coefficient of 91% or 9% dissimilarity (group IIb). Principle Component Analysis (PCA) results found a diversity of morphological characters with a total diversity of 51.3%. The PCA results showed the characteristics of the first group in the form of flower stalk length, weight, and number of flowers/series. The identifying characters for group IIa are the North-South canopy width and the East-West canopy width, while the identifying characters for group IIb are fruit length, width, and weight.